2010
DOI: 10.1016/j.chembiol.2009.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Rational Design of p53-Stabilizing Drugs: Probing the Surface of the Oncogenic Y220C Mutant

Abstract: The p53 cancer mutation Y220C induces formation of a cavity on the protein's surface that can accommodate stabilizing small molecules. We combined fragment screening and molecular dynamics to assess the druggability of p53-Y220C and map ligand interaction sites within the mutational cavity. Elucidation of the binding mode of fragment hits by crystallography yielded a clear picture of how a drug might dock in the cavity. Simulations that solvate the protein with isopropanol found additional sites that extend th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 57 publications
4
112
0
Order By: Relevance
“…S3), corresponding to a hit rate of 3.1%. A similar hit rate was also observed for a fragment-based, thermal-shift screening campaign of the ankyrin domain of Notch-1 receptor (3.2%) (40) and for a mutant of p53, Y220C (2.4%) (41). This hit rate includes both true and false hits.…”
Section: Resultssupporting
confidence: 49%
“…S3), corresponding to a hit rate of 3.1%. A similar hit rate was also observed for a fragment-based, thermal-shift screening campaign of the ankyrin domain of Notch-1 receptor (3.2%) (40) and for a mutant of p53, Y220C (2.4%) (41). This hit rate includes both true and false hits.…”
Section: Resultssupporting
confidence: 49%
“…Since the incompletely dehydrated backbone HB makes a soluble protein reliant on binding partnerships for the preservation of its fold , the two loops and the strand should be the putative epitopes for the ligand binding. Indeed, experimental studies have identified L2 and L3 as the DNA-binding surface via the direct interactions between Gln165, His168, Arg249 and DNA, and S7/ S8 as the surface for the binding of small molecules (Okorokov et al, 2009;Basse et al, 2010;Cho and Y., 1994;Wasielewski et al, 2006). Interestingly, after checking the water behavior surrounding Gln165, His168, Arg249 in all the systems, we find that there is no any highly structured water adjacent to these residues (distance <3.5 Å), but only motional waters.…”
Section: Distribution Of ''Hot Hydration Centers'' Of P53mentioning
confidence: 86%
“…It has been shown that the Y220C mutation lowers the melting temperature of the p53 protein, which allows a faster denaturation. Recently, a class of small molecules has been introduced that can restabilize the Y220C-mutated p53 protein by binding in its mutated pocket, thereby restoring its tumor-suppressive function [38]. In the era of personalized medicine, this specific mutation may guide therapeutic decisions in the future, especially in TP53 Y220C-mutated OPSCC.…”
Section: Discussionmentioning
confidence: 99%